Modeling and Simulation of Cultural Communication Based on Evolutionary Game Theory - Wenting Chen; Bopeng Jin (Complexity)
In the process of cultural dissemination, the dissemination of false information will have a negative impact on the entire environment. In this case, it is an effective method to regulate the behavior of cultural dissemination participants. Based on the community network structure and the improved classic network communication model, this paper constructs the susceptible-infected-recovered (SIR) model for the grassroots communication of engineering safety culture and discusses the law of grassroots transmission of engineering safety culture. The communication process is simulated, and it is concluded that a good engineering safety culture will be the first to be covered by low-level engineering safety culture in the process of dissemination. With a modularity coefficient of 0.5 as the boundary, it will affect the scale of good safety culture in different directions; the dissemination infection rate of low-level engineering safety culture changes in the same direction with the speed and scale of transmission; the maximum transmission scale of low-level engineering safety culture does not decrease with the increase of the initial value of the susceptible state. When the initial value of the immune state is 15%, the low-level safety culture scale is the lowest value of 0.135, which is the low initial value of employees with low-level engineering safety culture and is more conducive to control its maximum spread. It also puts forward management recommendations for the subjects and objects of the grassroots dissemination of engineering safety culture. This paper transforms cultural communication into an evolutionary game model, uses a game tree to describe it, and analyzes that the model has a Nash equilibrium point by adding a penalty function to the income matrix. This model can encourage cultural communication participants to take honest behaviors, effectively restrain the transmission of false information, and promote a virtuous circle of cultural communication.